Exploring the experiences of parents' involvement in supporting children with dyslexia in Maseru, Lesotho - Mahao, Nts’epase (Department of Social Development, 2025)
This study aimed to explore the experiences of parents' involvement in supporting children with dyslexia in Maseru, Lesotho. The research enquiry was rooted in Bronfenbrenner's Ecological Systems Theory for parental involvement. The study employed a qualitative research design, specifically phenomenology research approach, through face-to-face semi-structured interviews to gain insights and an understanding of parents' experiences regarding their involvement in supporting a child with dyslexia. The interviews were conducted with 12 participants who have lived in Maseru, Lesotho and their child was diagnosed with dyslexia. The diagnosis was carried out by their special education teacher. The sample was selected through purposeful sampling method. To analyse the data, thematic analysis was employed. The findings of this study revealed that parents' involvement in supporting their child is influenced by their lack of knowledge of dyslexia. As a result, their emotional experiences, experiences in seeking a diagnosis from professionals for their child, limited access to resources and information, their experiences with home-based involvement and parents' experiences with mainstream and special education needs (SEN) schools, were shaped by their lack of knowledge of dyslexia. The presence of a child with dyslexia was also noted to have an effect on family dynamics including the parent-child relationship, sibling relationship and parents' expectations. Furthermore, parents were observed to have insufficient support to help them in supporting their child, mainly relying on social support and spiritual support. The study emphasises the need for increased public awareness, policy development and institutional support to enhance parental involvement and improve outcomes for children with dyslexia in Maseru, Lesotho. Recommendations include developing dyslexia-specific interventions, training for educators and healthcare professionals (HPCs), and greater collaboration between parents, school, HCPs and policymakers.